Brentuximab vedotin resistance in classic Hodgkin's lymphoma and its therapeutic strategies: a review - Dayeeta Bera; Dattatreya Roy (SpringerOpen, 2024)
Abstract Background Bone marrow cancer has been at the forefront of cancer research. The propensity of cancers to extravasate to the bone makes it a very relevant topic in the topology of this heterogeneous disease. Our narrative review article addresses Brentuximab vedotin (BV) resistance in classic Hodgkin's lymphoma patients and discusses the current trends in the therapeutic process. The data have been collected from the works of well-established researchers, and the scientific evidence was abundantly supplemented with clinical and pre-clinical trial data. Although the findings cited are the latest, this review might not be very accurate for every population as the data from which this was derived have a population bias in several instances. The analysis has mostly been qualitative and interpretive, and quantitative evidence has only been used to explain the clinical trial results. We have divided our paper into the mode of action of BV, its probable and proven causes of resistance, and the therapeutic strategies employed to reverse them to ensure a systemic flow of information throughout the text. Main body Brentuximab vedotin is an antibody-drug conjugate with antineoplastic activity, used to target a novel immunophenotype tumor necrosis factor CD30. This factor is specific to the tumor-causing Reed-Sternberg cells in the inflammatory infiltrate. Though the drug had shown promise initially, the cancer was quick to develop resistance against the drug. We have analyzed and represented abundant statistical evidence to back this claim. The paper further discusses the role of the CD30 receptor, MDR1 gene, valine-citrulline linker, and tumor microenvironment in drug resistance. Lastly, we have discussed the possible therapeutics that can be used to overcome this resistance, discussing the well-established and trial-stage approaches taken in the endeavor. Conclusion The treatment is much better after the pursuit of reversing the drug resistance phenomenon. However, no therapeutic approach has been entirely successful in restricting the neoplastic property of cancer cells once and for all. This paper describes why that is so and how the heterogeneity of the disease complicates troubleshooting. We have tried to approach such problems through this specific example.